Kesetaraan Gender dalam Rumah Tangga Perspektif Alquran - Asya Dwina Luthfia; Siti Chodijah (Journal of Society and Development, 2021)
The purpose of this study is to examine gender equality in the household from the perspective of the Koran. The research method used in this article is qualitative with literature study and content analysis techniques to reach conclusions. The results and discussion of this study include general views of gender, gender equality in the Koran and gender equality in the household of the Koran perspective. The conclusion of this study is that gender equality in the household of the Qur’anic perspective means practicing an understanding of gender based on the correct understanding of the Qur’an regarding equality, justice, equality of husband and wife conditions in obtaining opportunities and their rights as human beings in the family as well as in achieving their goals of competing in goodness to the highest piety. This research is limited to the scope of the household, especially husband and wife. This study recommends the study of gender equality from the perspective of the Koran in other areas or specifically in the relationship of father or mother to children in the family.